Phospho-ERK is a biomarker of response to a synthetic lethal drug combination of sorafenib and MEK inhibition in liver cancer - Wang, Cun; Jin, Haojie; Gao, Dongmei; Lieftink, Cor; Evers, Bastiaan; Jin, Guangzhi; Xue, Zheng; Wang, Liqin; Beijersbergen, Roderick L.; Qin, Wenxin; Bernards, René (Journal of hepatology, 2018)
[Display omitted] •ERK2 inhibition was identified as an enhancer of the response to sorafenib in HCC.•Selumetinib increases the response of sorafenib in HCC cell lines with high p-ERK.•The synthetic lethal effect is derived from synergistic inhibition of ERK kinase.•The combination therapy is most likely to be effective in tumors with high p-ERK. Treatment of liver cancer remains challenging because of a paucity of drugs that target critical dependencies. Sorafenib is a multikinase inhibitor that is approved as the standard therapy for patients with advanced hepatocellular carcinoma, but it only provides limited survival benefit. In this study we aimed to identify potential combination therapies to improve the clinical response to sorafenib. To investigate the cause of the limited therapeutic effect of sorafenib, we performed a CRISPR-Cas9 based synthetic lethality screen to search for kinases whose knockout synergizes with sorafenib. Synergistic effects of sorafenib and selumetinib on cell apoptosis and phospho-ERK (p-ERK) were analyzed by caspase-3/7 apoptosis assay and western blot, respectively. p-ERK was measured by immunochemical analysis using a tissue microarray containing 78 liver cancer specimens. The in vivo effects of the combination were also measured in two xenograft models. We found that suppression of ERK2 (MAPK1) sensitizes several liver cancer cell lines to sorafenib. Drugs inhibiting the MEK (MEK1/2 [MAP2K1/2]) or ERK (ERK1/2 [MAPK1/3]) kinases reverse unresponsiveness to sorafenib in vitro and in vivo in a subset of liver cancer cell lines characterized by high levels of active p-ERK, through synergistic inhibition of ERK kinase activity. Our data provide a combination strategy for treating liver cancer and suggest that tumors with high basal p-ERK levels, which are seen in approximately 30% of liver cancers, are most likely to benefit from such combinatorial treatment. Sorafenib is approved as the standard therapy for patients with advanced hepatocellular carcinoma, but only provides limited survival benefit. Herein, we found that inhibition of the kinase ERK2 increases the response to sorafenib in liver cancer. Our data indicate that a combination of sorafenib and a MEK inhibitor is most likely to be effective in tumors with high basal phospho-ERK levels.